Use of Immunohistochemical Markers (HNF-1β, Napsin A, ER, CTH, and ASS1) to Distinguish Endometrial Clear Cell Carcinoma From Its Morphologic Mimics Including Arias-Stella Reaction. (July 2020) - Ji, Jennifer X.; Cochrane, Dawn R.; Tessier-Cloutier, Basile; Leung, Samuel; Cheng, Angela S.; Chow, Christine; Gilks, Blake; Huntsman, David G.; Hoang, Lynn N.
Abstract : The diagnosis of clear cell (CC) carcinoma of the endometrium can be challenging, especially when endometrioid (EC) and serous (SC) endometrial cancers exhibit nonspecific clear cell changes, in carcinomas with mixed histology and in the setting of Arias-Stella reaction (ASR). In this study, classic CC immunohistochemical markers (Napsin A, HNF-1β, and ER) and 2 recent novel markers, cystathionine gamma-lyase (CTH) and arginosuccinate synthase (ASS1), are assessed for their utility in distinguishing CC from its morphologic mimics. Tissue microarrays containing 64 CC, 128 EC, 5 EC with clear cell change, 16 SC, 5 mixed carcinomas, and 11 whole ASR sections were stained, with 12 additional examples of ASR stained subsequently. A cutoff of 70% and moderate intensity were used for HNF-1β, 80% of cells and strong intensity were used for CTH, and any staining was considered positive for the remaining markers. For differentiating CC from pure EC and SC, HNF-1β, Napsin A, and CTH all performed well. HNF-1β had higher specificity (99.3% vs. 95.1%) but lower sensitivity (55.8% vs. 73.1%) compared with Napsin A. CTH did not substantially outperform HNF- 1β or Napsin A (sensitivity 51.9%, specificity 99.3%). ASS1 and ER were not helpful (specificities of 60.1% and 22.6%). For differentiating CC from ASR, HNF-1β, Napsin A, and CTH stained a large proportion of ASR and were not useful. However, ER positivity and ASS1 negativity were helpful for identifying ASR (specificity 88.2% and 95.1%, respectively). EC with clear cell changes exhibited immunohistochemical patterns similar to pure EC (HNF-1β−, ER+, and CTH−). No markers were useful in confirming the CC components in mixed carcinomas.